Nanlooting ako a study of the lived experiences of the looters in the aftermath of super typhoon Yolanda - Bertos, Ma. Zarah Mae; Igmen Ma. Joy E.; Maceda, Ave Grace S.; Navarro, Gemmie Lyn B.; Rosal, Trisha May R. (Ma. Zarah Mae R. Bertos, May Joy E. Igmen, Ave Grace S. Maceda, Gemmie Lyn B. Navarro, Trisha May R. Rosal, 2014)
The looting experiences of those who engaged in looting are studied in terms of qualitative study and viewed in a psychological perspective. The looting experiences of individuals are undeniably understudied in the Philippine context. The current study utilized the thematic analysis to identify themes that arose from the interview of the six participants who identified themselves as looters. A phenomenological framework was used to study the lived experiences of the participants. Themes related to each participant were described from the data analysis. Based on the findings, looting is a complex phenomenon. Reasons for looting were a combination of external and internal influences.